Drying Technology Improvement Rengginang to Increase Turn Over Turn Season in Sambigede Village, Malang Regency - Irawan, Dani; Widiyadi; Mindarta, Erwin Komara; Wisnu, Andri; Froidah, Nadia (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The solution to the problems above that we offer is "Design of the Rengginang Drayer with Corn Cob Waste Energy as a Solution for Drying Rengginang in the rainy season in the Cap Krisna Rengginang industry in Sambigede Village, Sumberpucung District, Malang Regency". The results of this design are intended to increase income, especially community industrial groups in Sambigede Village, Sumberpucung, Malang Regency. The results of this design are the result of developing campus intellectual products that are in accordance with the urgency of the needs of the village community in the form of Rengginang drayer technology.